Apuntes sobre Política Exterior de Costa Rica Tendencias, retos y cursos de acción. - Flores Zúñiga, Francisco Javier (2015)
This paper begins with an examination ofthe historical situation of our foreign policy,describe the context of internationalrelations of this century and the processof globalization and its effect on the roleof the state, which cannot avoid the internationalizationof domestic law. Reviewthe role of the International Cooperation,warns of the need to democratize our foreignpolicy, and particularized need toimplement a strategy of the LegislativeAssembly on control of foreign policy.